Comparing the perceptions and opinions of the 2007 and 2019 Canada's food guides among parents of young children - Ramuscak, Alyssa V.; Ma, David W. L.; Forbes, Laura E.; Duncan, Alison M.; Sadowski, Adam; Haines, Jess (Frontiers in Public Health, 2022)
Background The Canada's Food Guide (CFG) is recognized as the most prominent authoritative guideline for healthy eating in Canada. In 2019, Health Canada released the latest iteration of the CFG with substantial changes to its messaging and format from the previous 2007 CFG. Objective This study compared the awareness, use, knowledge, and opinions of the 2007 and 2019 CFGs among parents with children aged 18 months to 5 years who are participants in a family-based intervention trial, the Guelph Family Health Study. Methods The sample consisted of 327 parents (59% women) who responded to questions about the 2007 CFG and 177 parents (60% women) who responded to questions about the 2019 CFG. Parents' awareness and knowledge of the 2007 and 2019 CFGs were compared using Pearson's Chi-Square, while parents' opinions of the two CFGs were compared using Wilcoxon Rank-Sum tests. To describe and provide context about how parents used the 2007 and 2019 CFG descriptive analysis was used. To analyze the open-answer comments parents provided for the 2007 and 2019 CFGs thematic coding was used. Results Awareness of the 2007 and 2019 CFGs was high with 94.5 and 90.4% of parents reported having heard about the 2007 and 2019 CFGs, respectively. Knowledge of the plate proportion recommendations in the 2019 CFG was significantly higher than knowledge of the recommended number of servings in the 2007 CFG with 93.4% of parents identifying the Vegetable and Fruit Plate Proportions in the 2019 CFG. Parents identified that the 2019 CFG was a helpful and trustworthy resource, and that it was easier to follow and understand, and more representative of their culture and traditional foods than the 2007 CFG. Conclusion Our results suggest that parents' knowledge of the 2019 CFG recommendations was higher than for the 2007 CFG recommendations. Parents also had more positive opinions about the 2019 CFG as compared to the 2007 CFG. Future research is needed to explore whether these higher levels knowledge of the 2019 CFG recommendation translate to healthier eating patterns among Canadian families.